Peptide translocation across asymmetric phospholipid membranes - Bartoš, Ladislav; Vácha, Robert (Biophysical journal, 2024)
The transport of molecules across cell membranes is vital for proper cell function and effective drug delivery. While most cell membranes naturally possess an asymmetric lipid composition, research on membrane transport predominantly uses symmetric lipid membranes. The permeation through the asymmetric membrane is then calculated as a sum of the inverse permeabilities of leaflets from symmetric bilayers. In this study, we examined how two types of amphiphilic molecules translocate across both asymmetric and symmetric membranes. Using computer simulations with both coarse-grained and atomistic force fields, we calculated the free energy profiles for the passage of model amphiphilic peptides and a lipid across various membranes. Our results consistently demonstrate that while the free energy profiles for asymmetric membranes with a small differential stress concur with symmetric ones in the region of lipid headgroups, the profiles differ around the center of the membrane. In this region, the free energy for the asymmetric membrane transitions between the profiles for two symmetric membranes. In addition, we show that peptide permeability through an asymmetric membrane cannot always be predicted from the permeabilities of the symmetric membranes. This indicates that using symmetric membranes falls short in providing an accurate depiction of peptide translocation across asymmetric membranes.
Keywords: buněčná membrána; Peptides; simulace molekulární dynamiky; Lipid Bilayers; fosfolipidy; lipidové dvojvrstvy; Cell Membrane; Molecular Dynamics Simulation; Phospholipids; peptidy